2022
DOI: 10.3390/biology11071042
|View full text |Cite
|
Sign up to set email alerts
|

Ecotourism Disturbance on an Endemic Endangered Primate in the Huangshan Man and the Biosphere Reserve of China: A Way to Move Forward

Abstract: The primary purpose of the Man and the Biosphere Program is the sustainable development of both the economy and nature conservation activities. Although the effectiveness of eco-tourism to reach this goal has been proposed, due to the lack of long-term monitoring data and a model species, there has been no obvious mechanism to evaluate the effectiveness of this policy. This study explored the effectiveness of the sustainable development policy of HMBR based on 30 years data of monitoring the Tibetan macaque, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…For example, a recent study reported that 16 of the 104 groups of critically endangered western black crested gibbons (Nomascus concolor) are located nearby but outside of the Wuliangshan National Nature Reserve in Yunnan, China (Fan et al, 2022). A similar situation exists for species such as François' Langurs (Endangered) (Zhou & Huang, 2021), golden snub-nosed monkeys (Endangered) (Yu et al, 2022), and Tibetan macaques (Near Threatened) (Li, Yang, et al, 2022), with many populations ranging outside of PAs. Thus, there is an imperative to expand the national system of PAs in China to safeguard threatened populations and species (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…For example, a recent study reported that 16 of the 104 groups of critically endangered western black crested gibbons (Nomascus concolor) are located nearby but outside of the Wuliangshan National Nature Reserve in Yunnan, China (Fan et al, 2022). A similar situation exists for species such as François' Langurs (Endangered) (Zhou & Huang, 2021), golden snub-nosed monkeys (Endangered) (Yu et al, 2022), and Tibetan macaques (Near Threatened) (Li, Yang, et al, 2022), with many populations ranging outside of PAs. Thus, there is an imperative to expand the national system of PAs in China to safeguard threatened populations and species (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 97%